CYBERLOAFING DITINJAU DARI ROLE AMBIGUITY PADA KARYAWAN PT. FURNILUX INDONESIA SEI RAMPAH - Tri Santy Erika (Psikologi Prima, 2018)
This study aims to test if there is a positive relationship between role ambiguity and cyberloafing, assuming higher role ambiguity, the lower cyberloafing is, on the other hand, the lower the ambiguity role, the lower is cyberloafing. The research subjects were all employees at PT. Furnilux Indonesia consisting of 105 people or commonly termed as saturated sampling method. Data were obtained from the scale to measure role ambiguity and cyberloafing. The calculations performed by prerequisite analysis uses shows that r = 0.544, and p = 0.000 (p<0.05) showing that there was a positive relationship between role ambiguity and cyberloafing. The results of this study indicated that the contribution (R2) is given by the variable role of ambiguity tons of cyberloafing up to 29.6 percent, the remaining 70.4 percent was affected by other variable not studied. Based on the results of this study can be concluded that the hypothesis can be accepted.